2022
DOI: 10.3390/jcm11195746
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet Is Associated with a More Favorable Left Ventricular Geometry in Patients with End-Stage Kidney Disease

Abstract: Introduction. The aim of the study was to examine the impact of adherence to a Mediterranean-style diet (MD) on left ventricular hypertrophy (LVH) and cardiac geometry in chronic kidney disease patients on dialysis (CKD-5D), given the high prevalence of cardiovascular morbidity in this population. Methods. n = 127 (77 men and 50 women) CKD-5D patients (69 on hemodialysis and 58 on peritoneal dialysis) with a mean age of 62 ± 15 years were studied. An MD adherence score (MDS) (range 0–55, 55 representing maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Seventeen studies were further excluded as they either did not report outcomes of interest, excluded dialysis patients, did not evaluate the diet of interest, or had no separate analysis of ESKD outcomes. The final analysis included seven articles [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], consisting of 9400 ESKD patients, from which 8395 were HD patients and 1005 were peritoneal dialysis (PD) patients. The literature retrieval, review, and selection process are demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen studies were further excluded as they either did not report outcomes of interest, excluded dialysis patients, did not evaluate the diet of interest, or had no separate analysis of ESKD outcomes. The final analysis included seven articles [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], consisting of 9400 ESKD patients, from which 8395 were HD patients and 1005 were peritoneal dialysis (PD) patients. The literature retrieval, review, and selection process are demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Higher adherence to a Mediterranean diet was associated with decreased adverse cardiovascular outcome markers as measured by LVH in ESKD patients [ 16 ]. Becharaki et al [ 16 ] also showed that a higher Mediterranean diet score was associated with a lower prevalence of crescentic and eccentric cardiac geometry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations